(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In the era of digital transformation, cloud computing has become integral to modern enterprises, offering scalable resources and flexibility. However, this rapid adoption has also introduced a new landscape of security challenges, including data breaches, insider threats, and misconfigurations, all of which can compromise sensitive information and disrupt operations. Traditional security measures often fall short in addressing these complex threats, prompting the need for more advanced solutions. This article explores the pivotal role of AI-driven security protocols in fortifying cloud infrastructures against evolving cyber threats. By leveraging AI, cloud engineers can implement real-time threat detection, automate incident responses, and enhance identity and access management (IAM), significantly reducing the risk of unauthorized access and data leakage. AI’s capability to analyze vast amounts of data and identify anomalies allows for more proactive security measures, adapting to new threats as they emerge. Additionally, AI can streamline the management of data encryption and privacy, ensuring compliance with regulatory standards. The article also examines implementation strategies, emphasizing the integration of AI with existing security frameworks and the importance of continuous learning and collaboration between AI systems and human experts. As cloud environments grow increasingly complex, AI-driven security protocols represent a critical advancement in safeguarding digital assets. Through case studies and analysis, this research highlights the effectiveness of AI in enhancing cloud security and the future trends that will shape its ongoing development.